HUBUNGAN METODE BIRTH BALL TERHADAP LAMA PERSALINAN KALA I FASE AKTIF DI KLINIK PRATAMA BIDAN DELIANA TAHUN 2025 - Diana Rifka Yulia Wahyuni; Ummu Luthfiyah; Siti Halimah; Tiffany Atia Aristy (Ensiklopedia of Journal, 2025)
Labor is the birth of a baby, placenta, and amniotic membranes from the uterus to the outside world. The cause of complications in childbirth that causes increased mortality and morbidity in the mother and fetus is prolonged labor. The high number of old events during the active phase I in Pekanbaru.This study uses a quasi-experimental research method. The population in this study were all third trimester pregnant women in the working area of Sidomulyo Health Center. The sample in this study were 30 respondents with purposive sampling technique. This research instrument uses partographs and observation sheets to assess the length of the first stage of the active phase. Data analysis was univariate, bivariate and multivariate.The results showed that there was no effect between maternal age and the length of the first stage (p = 0.322), there was an influence between maternal age and the length of the first stage (p = 0.014). There is an effect of Birthball and parity intervention on the length of the first stage in the Work Area of the Sidomulyo Public Health Center. Based on the results of this study, the most influential is parity on the length of the first stage.The conclusion of this study is that there is no influence between maternal age and the length of the first stage, there is an influence between maternal age and the length of the 1st stage. It is hoped that it can be a reference for midwives in providing midwifery care to improve the skills of midwives in carrying out normal delivery assistance in order to reduce morbidity and mortality rates. pregnant women and neonates.Keywords: Birthball, First Kala Lama, Parity